Onset response of bupivacaine 0.5% which has been added with sodium bicarbonate on epidural block (Medical Journal of Indonesia, 2005)
There are many advantages in using epidural anesthesia technique.However, there are also some constraints, such as the relatively long onset, particularly in the case of bupivacaine.Whereas the need of a rapid onset ofanesthesia technique for emergency cares is increasinglately. The objectiveof this studywas to find a method to hasten theonset of bupivacaine. This is a cross sectionalrandomized double blind controlled clinical trial performed on 40 patients who would undergo lower abdomen and extremity surgerywith epidural block.We evaluated the onset of action of bupivacaine which hasbeen added with sodium bicarbonate. Consecutive sampling method was appliedto get the sample. Thecriteria of sample are ASA I –II patient, agedof 20-60 years old, 50-60 kg of weight, 150-170 cm of height. Patients wereallocated randomly into two groups. The treatment group would get epidural block using mixtureof 20 cc of bupivacaine 0,5% + 0.5 cc of sodium bicarbonate 1.4 %, whereas the control group received20 cc bupivacaine 0.5 % + 0.5 cc aqua bides.Time to reach sensoric blockat the level of thoracal 10 dermatomeusing the pinprick methodand time to reach motoric blockade usingthe bromage scalewas recorded. The result of this study showed a significant shortening of theonset of sensory blockade (p<0.05) in the treatment group (10.2+1.4 minutes) compared with the control group (19.5+1.3 minutes). The onset of motor blockade had also a significant shortening (p<0.05) in the treatment group(13.3+1.6 minutes) compared with the control group (23.0+1.2 minutes). It was concluded that the additionof sodium bicarbonate can hasten the onset of bupivacaine on epidural block. (Med J Indones 2005; 14: 7-10) Keywords : onset response, bupivacaine 0.5%, sodium bicarbonate, epidural block